2020
DOI: 10.1136/jim-2019-001173
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Impact of a Pharmacist-Led Antimicrobial Stewardship Initiative Evaluating Patients with Clostridioides Difficile Colitis

Abstract: Clostridioides difficile is the most common cause of healthcare-associated infection and gastroenteritis-associated death in the USA. Adherence to guideline recommendations for treatment of severe C. difficile infection (CDI) is associated with improved clinical success and reduced mortality. The purpose of this study was to determine whether implementation of a pharmacist-led antimicrobial stewardship program (ASP) CDI initiative improved adherence to CDI treatment guidelines and clinical outcomes. This was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 15 publications
(46 reference statements)
0
21
0
Order By: Relevance
“…Of 16 studies that reported "audit and feedback" as an intervention, five did not meet the definition in our review [34,53,55,56,72], even though they described their intervention as "audit and feedback" in the title or the methods. The intervention in these five studies was educational outreach using review cases with the provision of recommendations for change.…”
Section: (3) What Interventions Did Pharmacists Use To Improve Antimi...mentioning
confidence: 98%
See 3 more Smart Citations
“…Of 16 studies that reported "audit and feedback" as an intervention, five did not meet the definition in our review [34,53,55,56,72], even though they described their intervention as "audit and feedback" in the title or the methods. The intervention in these five studies was educational outreach using review cases with the provision of recommendations for change.…”
Section: (3) What Interventions Did Pharmacists Use To Improve Antimi...mentioning
confidence: 98%
“…The majority (n=39) of studies described the mode for providing pharmacist recommendations, 30 of which used verbal communication (face-toface contact, interaction during ward round, or by mobile phone) [23, 24, 27, 30-33, 36-39, 41-44, 46, 50, 51, 53-55, 57, 59, 60, 62, 66, 69-71, 73]. Nine additional studies used nonverbal (written recommendations in medical charts or electronic medical records) (n=5) [25,35,45,56,65] and both verbal and non-verbal communication (n=4) [28,52,58,72].…”
Section: (3) What Interventions Did Pharmacists Use To Improve Antimi...mentioning
confidence: 99%
See 2 more Smart Citations
“…ASP is instituted to promote the appropriate use of antimicrobials, improve patient outcome, reduce microbial resistance, and decrease the spread of infection caused by multidrug-resistant organisms (Charani et al, 2019). Meanwhile, the inclusion of clinical pharmacists in ASP has been shown to result in significant improvement in terms of the quality of antibiotic use from various aspects, such as improving guidelineconcordant antimicrobial prescribing (Smith et al, 2018;Wang et al, 2018;Fay et al, 2019;Bishop et al, 2020), lessening the emergence of multidrug resistance (Li et al, 2017), shortening the days of antibiotic therapy (Wirtz et al, 2020), reducing the hospital stay of patients (Sadyrbaeva-Dolgova et al, 2020), and decreasing patients mortality (Li et al, 2017). ASP in China was initiated in 2011 with the promulgation of the Guideline for Clinical Application of Antimicrobial Agents (GCAAA), which required clinical pharmacists to participate in the management of antimicrobials, particularly in special antibiotics (vancomycin, carbapenem, tigecycline).…”
Section: Introductionmentioning
confidence: 99%